12-4h=6

Simple and best practice solution for 12-4h=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-4h=6 equation:


Simplifying
12 + -4h = 6

Solving
12 + -4h = 6

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -4h = 6 + -12

Combine like terms: 12 + -12 = 0
0 + -4h = 6 + -12
-4h = 6 + -12

Combine like terms: 6 + -12 = -6
-4h = -6

Divide each side by '-4'.
h = 1.5

Simplifying
h = 1.5

See similar equations:

| j-(-17)=30 | | 5-3*x=20 | | t+13.4=-4.5 | | 1p-5=8 | | 4(p+5)=7 | | 36t^2=9 | | -6n+5n=-3 | | 4(p+-5)=7 | | (6x-6)(4x+9)=0 | | -6r+5s+2t=-11 | | 3(x)=8.25 | | 3x^2-6x+4y^2-13=0 | | 12(y+2)=36 | | 8(x)=8.25 | | 8x+7=127 | | 170+0.25x=375 | | 7200=(756)R(2.5) | | x-8.6=4.1 | | y+5x=-10 | | -2/3+x=22/3 | | 5665*x=100000 | | 6z+17=-7 | | 12d-7+3d=19+14d | | 49x^2-10=0 | | x-.07=139500 | | -2(x-1)-4=-4(1+x)+2x+2 | | x+100=299 | | 2x-3(2x+4)=-6x+10 | | r+34=21 | | 3y+5(-3)y-3=27 | | 4u-w=u-5w | | 79/7=x-5/7 |

Equations solver categories